Implementation of the Cooperative Model of the Teams Games Tournament Type Assisted by Jellyfish Hunting Media to Improve Mathematics Learning Outcomes of Class III SDN 22/II Pematang Panjang - Maulidha Risma Putri; Zulqoidi R. Habibie; Abdulah Abdulah (CV. Master Literasi Indonesia, 2025)
This Classroom Action Research was carried out with third-grade students at SDN 22/II Pematang Panjang, motivated by the low learning process and outcomes. This was evident from the learning activities that did not yet align with the demands of the Merdeka Curriculum and the average daily test scores that were still below the school's KKTP standard of 70. To address this issue, a cooperative learning model of the Teams Games Tournament (TGT) type supported by the “jellyfish hunting” media was implemented. The purpose of this study was to improve students' cognitive processes and learning outcomes in decimal number material. The method used was Classroom Action Research (CAR), conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The research subjects were 23 students. Data collection techniques included observation and tests, with instruments in the form of observation sheets and test sheets. Observation data were analyzed descriptively, while test data were analyzed using a one-sample t-test with the Statistical Package for the Social Sciences (SPSS). The results showed that the implementation of the cooperative TGT model supported by the jellyfish hunting media in geometry material was categorized as very good. Teacher assessment process from cycle I to cycle II increased by 17%, reaching 97%. Student process performance increased by 30%, with a final percentage of 87%, exceeding the process success indicator of 75%. Students' learning outcomes in the initial observation were only 39%. After applying the TGT model, mastery increased to 61% with an average score of 71 in cycle I. In cycle II, mastery reached 83% with an average score of 82. It can be concluded that the application of the cooperative TGT model supported by the jellyfish hunting media improved the learning process and student outcomes by 44% from the initial condition.